2020
DOI: 10.3390/ijerph17228580
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Training Loads and Selected Blood Parameters in Professional Soccer Players during a 12-Day Sports Camp

Abstract: The main purpose of this study is to assess the relations between training loads and selected blood parameters in professional soccer players during a preseason sports camp. Fifteen professional soccer players (age: 24.3 ± 5.25 year; height: 182.6 ± 6.75 cm; weight: 76.4 ± 6.72 kg) participated in the 12-day training camp. All the training sessions and friendly games were accurately analyzed with a GPS system. Blood samples were taken from the players and analyzed before the camp (PRE), in the middle (MID), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
0
14
1
Order By: Relevance
“…The studies mentioned above support the results of our study. However, these results differ from the study published by Radzimiński et al [ 70 ], where it was found that elevated CRP values were not detected in soccer players during a pre-season sports camp (pre: 1.44 ± 0.7 mg/L, post: 0.83 ± 0.34 mg/L), i.e., above the reference range (<5.0 mg/L).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The studies mentioned above support the results of our study. However, these results differ from the study published by Radzimiński et al [ 70 ], where it was found that elevated CRP values were not detected in soccer players during a pre-season sports camp (pre: 1.44 ± 0.7 mg/L, post: 0.83 ± 0.34 mg/L), i.e., above the reference range (<5.0 mg/L).…”
Section: Discussioncontrasting
confidence: 99%
“…Increased levels of oxidative stress are closely associated with markers of muscle damage with high inflammation [ 59 ]. CRP is the most common inflammation molecule of the body’s acute phase response, and it increases the inflammatory response to various stimuli that initiate the acute phase response [ 47 , 69 , 70 ]. In our study, significant increases were found in CRP values after post-pre-season compared to pre-pre-season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the nature of professional soccer, players are at particular risk for vitamin D insufficiency. The reason for this is the large number of official matches played during the annual training cycle where the difference between the pre-season and competitive periods has become indistinct and the detraining period sometimes last less than two weeks [ 31 ]. The periodization was more widely observed and respected in training periods of young soccer players [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory biomarkers as C-reactive protein (CRP), an acute-phase inflammatory protein, and high-energy enzyme biomarkers as creatin kinase (CK), a high-energy phosphate enzyme, reportedly have a dose-dependent behaviour with a transient increase after a 24-h marathon and ultra-marathon (Kim et al, 2009). Lactate dehydrogenase (LDH) is a key glycolytic enzyme that increases with increased training loads (Radzimiński et al, 2020).…”
Section: Introductionmentioning
confidence: 99%